2011
DOI: 10.3347/kjp.2011.49.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Resistance toToxoplasma gondiiInfection in Mice Treated with Silk Protein by Enhanced Immune Responses

Abstract: This study investigated whether elevated host immune capacity can inhibit T. gondii infection. For this purpose, we used silk protein extracted from Bombyx mori cocoons as a natural supplement to augment immune capacity. After silk protein administration to BALB/c mice for 6 weeks, ratios of T lymphocytes (CD4+ and CD8+ T-cells) and splenocyte proliferative capacities in response to Con A or T. gondii lysate antigen (TLA) were increased. Of various cytokines, which regulate immune systems, Th1 cytokines, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…In particular, it has been reported that certain protein food products, including lactoferrin, soybean protein fraction (a milk-derived protein casein), contain immune-modulating functions and thus increase NK cell activity in immunocompromised mice, stimulate the cellular immune response, and exert mitogenic effects ( 31 32 33 34 ). Silk protein has also been proposed as a bioactive substance and is effective at reducing blood pressure, exhibiting anti-tumor activity, treating atopic dermatitis, promoting insulin release, and enhancing innate immune responses ( 14 18 35 36 37 ). In this regard, we explored the effects of silk peptide on immune capability in vivo , especially on NK cell activity, in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been reported that certain protein food products, including lactoferrin, soybean protein fraction (a milk-derived protein casein), contain immune-modulating functions and thus increase NK cell activity in immunocompromised mice, stimulate the cellular immune response, and exert mitogenic effects ( 31 32 33 34 ). Silk protein has also been proposed as a bioactive substance and is effective at reducing blood pressure, exhibiting anti-tumor activity, treating atopic dermatitis, promoting insulin release, and enhancing innate immune responses ( 14 18 35 36 37 ). In this regard, we explored the effects of silk peptide on immune capability in vivo , especially on NK cell activity, in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic changes in splenocytes were analyzed using flow cytometry [ 44 ]. Spleens were gently crushed through a stainless-steel mesh under aseptic conditions to remove tissue debris.…”
Section: Methodsmentioning
confidence: 99%
“…After an acclimation period of 1 week, mice were housed in an animal facility equipped with SPF conditions at the Seoul National University College of Medicine [11]. Seven-week-old C57BL/6 mice were infected with G. seoi metacercariae.…”
mentioning
confidence: 99%
“…Specific pathogen-free (SPF) female C57BL/6 mice were purchased from Koatech Laboratory Animal Center (Pyeongtaek-shi, Gyeonggi-do, Korea). After an acclimation period of 1 week, mice were housed in an animal facility equipped with SPF conditions at the Seoul National University College of Medicine [ 11 ]. Seven-week-old C57BL/6 mice were infected with G. seoi metacercariae.…”
mentioning
confidence: 99%